Citrobacter freundii as a cause of acute suppurative thyroiditis in an immunocompetent adult female - Gursimran Kaur Mohi; Priya Datta; Jagdish Chander; Arjun Das (Wolters Kluwer Medknow Publications, 2017)
Acute suppurative thyroiditis (AST) is an uncommon condition, in the patients with preexisting thyroid disease or immunosuppression. The most common cause of AST is bacterial, and the most common bacteria are Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Klebsiella species. Due to various complications such as septicemia, septic thrombophlebitis, necrotizing mediastinitis, or pericarditis, prompt diagnosis and treatment are the keys to reduce mortality and morbidity. Here, we describe a case of a 40-year-old female with AST caused by Citrobacter freundii. This is the first case report of isolation of this bacterium from AST in the world. It is important to differentiate AST from subacute thyroiditis, which is far more frequent and runs a more prolonged course. Various risk factors which predispose to this condition include structural abnormality in the thyroid gland or thyroid disease and immunocompromised state. The route of infection may be either hematogenous or lymphatic seeding. With the increase in number of immunocompromised patients, the cases of AST will increase.